PENDAMPINGAN PENGELOLAAN DANA ANAK YATIM DI MASJID AL-INAYAH - Mutamakin, M.; Faishol, Riza; Jaya, Rahmat; Dhamayanti, Sylvia Kartika; Pranawukir, Iswahyu (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
So far, the management of orphan funds at Al-Inayah mosque has been made bookkeeping globally so that there are difficulties in making financial reports to the community, planning and managing funds that are not neatly organized so that the management is considered unaccountable and transparent. So that a mentoring activity or counselor is needed that can help managers more precisely in choosing and sorting out various priorities for orphan needs, can plan the use of funds properly, carry out appropriate activities, correct evaluation, neat organization, compile financial statements in accordance with financial accounting standards, accountable and transparent. The methods used are problem analysis, formation & socialization of new management, provision of financial management materials &; financial transparency, coordination of orphan guardians & account creation, and evaluation. The result obtained is that the implementation of assistance in the management of orphan funds at the Al-Inayah mosque in Melik hamlet, Parijatah Kulon village has gone according to plan, runs in an orderly manner, smoothly and is able to provide benefits and convenience to mentoring participants and orphans. This community service activity needs to be continued in the future so that the ability to manage orphans' funds becomes even better.